Fostering autonomy in vocational college students: A fusion of metacognitive strategies and social cognitive learning theory - Xiaotian, Wang; Jantharajit, Nirat; Srikhao, Sarit (Asian Journal of Contemporary Education, 2024)
The aim of this study is to investigate how to foster vocational college students’ autonomy in learning by integrating metacognitive strategies and social cognitive learning theory. The study uses social cognitive learning theory to look at metacognitive strategies in a systmematic and thorough way. It looks for similarities and places where the two can be combined in order to come up with a new and effective way to teach. 1) The integration of metacognitive strategies and social cognitive learning theory offers innovative perspectives and strategies for educational practice, fostering students’ autonomy and social adaptability; 2) Through dual monitoring of cognition, nurturing social cognition, and deep integration of metacognitive strategies, educational practices can enhance students’ cognitive control and social interaction abilities. 3) Future educational endeavors should focus on eliciting metacognitive awareness, integrating metacognitive strategies into teaching practices, and emphasizing social cognitive elements in evaluation mechanisms to address the complex challenges of modern education. 4) The fusion of these theories presents challenges in theoretical integration, teaching practices, assessment systems, and professional development, requiring innovative solutions and comprehensive support for educators and students alike. This study emphasizes the importance of teaching students reflective learning practices and actively cultivating metacognitive regulation abilities through cooperative learning. Furthermore, it underscores the necessity of integrating social cognitive aspects into assessment practices, thereby proposing an innovative educational approach.